Hernia of the xiphoid process - V. V. Ivlev (Вестник хирургии имени И.И. Грекова)
Hernia of the xiphoid process refers to rare variants of hernial protrusion. For the period from 1914 to the present, only 11 cases have been described in the official Russian-language literature. Hernial gates are either a defect of a rounded shape directly in the xiphoid process, or splitting of the xiphoid process by the type of «horns». The contents are most often preperitoneal lipoma, and 2 cases have also been described when the contents were a strand of the large omentum and a fatty appendage of the transverse colon. The risk of infringement with such hernias is minimal. Operational tactics, despite the development of modern minimally invasive techniques, still remains controversial due to the peculiarities of the fit to the xiphoid process of the peritoneum and the thoracic own fascia to the periosteum of the sternum process. This paper presents a clinical case of a patient sought medical help for an increase in education in the xiphoid process within 4 months.